Beyond mindfulness: Buddhist psychology and the Abhidharma - Kelly, Brendan D. (Journal of spirituality in mental health, 2023)
Buddhist psychology increasingly informs mental healthcare through therapies such as cognitive behavioral therapy (CBT) and dialectical behavior therapy (DBT), as well as explicitly Buddhist therapies. The central tenets of Buddhist psychology are explored in the Abhidharma, a collection of psychological works from the traditional canon. The Abhidharma includes detailed expositions of the structure of consciousness; the natures of active cognitive processes and passive states; the relationships between material and mental phenomena, conditionality, and “dependent arising”; and the practice of meditation. These concepts are increasingly relevant owing to the continued emergence of psychotherapeutic practices (e.g., mindfulness) with significant roots in Buddhism.